Pengembangan E-Modul Interaktif Berbasis Android untuk Siswa Kelas VII SMP Materi Penyajian Data - Fitriyah, Awwalul; Manoy, Janet Trineke; Fiangga, Shofan (Program Studi S1 Matematika UNESA, 2024)
Technological developments in the world of education are growing rapidly, one of which is electronic modules (e-modules) which can be alternative learning media used in the teaching and learning process. This study aims to develop Android-based interactive e-module learning media that meets valid, practical, and effective criteria. It uses the ADDIE model, which consists of five stages: analysis by performance, students, curriculum, and media. The design stage involves material preparation, instrument manufacturing, flowcharts, and storyboards. The development phase involves interactive e-modules based on Android, media validation, revision, and limited trials. The implementation phase involves implementing the e-module for class VII students at SMPN 26 Surabaya. The Evaluation stage is carried out by analyzing the results of the research that has been done.The results of the development of this media are suitable for use based on predetermined criteria. The first criterion is that learning media has been declared very valid with a score of 82.7% for the design, a score of 81.2% for the material, and the validity of the test questions which get a score of 86.1%. The second criterion is that learning media is declared practical by the percentage of student response questionnaires of 77.7%. The third criterion is that the learning media is declared effective and there is a significant difference between the results of student scores before and after using the e-module as evidenced by the average N-Gain score of 0.79.